Transformação de processos para o aumento de eficiência na SEFAZ: um estudo de caso - Saraiva, Bruno Moreira (2024)
Process transformation is a powerful tool to impact the reality of a situation by improving and expanding the ways of executing a job or a process. With the incessant search for efficiency in Public Administration, process transformation becomes an allied tool in achieving the goals established by public managers. This, the dissertation presents a case study conducted at the Treasury Department of the State of Ceará, focusing on the transformation of the State Payroll process, initiated in mid-2022, The process reached its first outcomes in September 2023. The case study highlights both qualitative and quantitative improvements, demonstrating the extensive benefits for the Secretariat and the State of Ceará. In the context of several changes, the most notable variable was the Treasury account balance, which was utilized to cover recurring and unpredictable payroll expenses.